From let it be to it must be love: the development of a choir for patients and staff at a high secure hospital. Issue 1 (2nd January 2017) - Merrick, Ian; Maguire, Alex
Abstract: Introduction: Patients in high secure services are necessarily excluded from the rest of society, a situation which nevertheless risks them becoming further alienated and unwell. Recent policy developments aimed at making mental health services more recovery focused and socially inclusive challenged therapists to find ways to introduce them in a high secure setting. Method: A joint project initiated by the music therapist and a clinical specialist occupational therapist at a high secure hospital attempted to put these principles into practice by involving patients and staff in a weekly choir, which the members decided would be called the Vocal Group. The group worked together to decide its direction and purpose. Results: The patients and staff felt that the group was inclusive, enjoyable, levelling and recovery focused. The group performed at the first ever patient conference at the hospital in October 2010. Despite dissolving in 2011, the choir started afresh, performing again at the 150 th anniversary of the hospital in 2013, and continues as a high profile therapeutic intervention within the hospital. Discussion: The new choir has been developed using lessons learned from the earlier project to ensure that the therapeutic benefits continue to be felt by both the patients and the organisation as a whole.